2020
DOI: 10.1101/2020.06.06.20122341
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effect of tocilizumab in hospitalized patients with severe pneumonia COVID-19: a cohort study

Abstract: Background. Tocilizumab, a drug targeting interleukin-6 administrated in the right timeframe may be beneficial in coronavirus-disease-2019 (COVID-19). We aimed to assess its benefit, drawing from observations in compassionately treated patients. Methods: In a retrospective case-control study, treatment effect (tocilizumab 400mg, single-dose) was assessed using three statistical methods: propensity-score matching, Cox multivariable survival and inverse probability score weighting (IPSW) analyses. Were included… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 15 publications
0
23
0
Order By: Relevance
“…Besides, infectious complications were observed in 32.4% of TCZ group, and 14.9% of TCZ patients were accompanied by severe events (sepsis cases, candidemia, lung abscess or epidural abscess) [80]. Another propensity-score matched cohort study (84 vs. 84 severe patients; 400 mg single-dose) came to similar conclusions in improving overall survival (adjusted HR = 0.26, 95% CI 0.135-0.51, P = 0.0001), and it did not report any adverse effect [81]. A cohort study found TCZ therapy (dose: 8 mg/kg) in hyperglycaemic (n = 31) failed to attenuate risk of severe outcomes as it did in normoglycaemic patients (n = 47) (P < 0.009), and it did not report any adverse effect [82].…”
Section: Implementation Considerationsmentioning
confidence: 82%
“…Besides, infectious complications were observed in 32.4% of TCZ group, and 14.9% of TCZ patients were accompanied by severe events (sepsis cases, candidemia, lung abscess or epidural abscess) [80]. Another propensity-score matched cohort study (84 vs. 84 severe patients; 400 mg single-dose) came to similar conclusions in improving overall survival (adjusted HR = 0.26, 95% CI 0.135-0.51, P = 0.0001), and it did not report any adverse effect [81]. A cohort study found TCZ therapy (dose: 8 mg/kg) in hyperglycaemic (n = 31) failed to attenuate risk of severe outcomes as it did in normoglycaemic patients (n = 47) (P < 0.009), and it did not report any adverse effect [82].…”
Section: Implementation Considerationsmentioning
confidence: 82%
“…In this regard, recent real-world observational studies of high quality from Italy, Spain, France and the US, indicated that TCZ might reduce ICU admissions, mechanical ventilator use, and risk of death, when compared to control group only treated with SOC [15][16][17][18][19][20][21][22][23][24]. Moreover, Moreno-García et al [16] conclude that the beneficial effect of TCZ might be especially shown in the subset of severely-ill non-intubated COVID-19 patients at early stage of the systemic hyperinflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, there is an emerging number of additional observational studies of higher quality from Italy, Spain, France and the US, either recently published or registered in the medRxiv repository [15][16][17][18][19][20][21][22][23][24]. These studies mostly assessed the use of TCZ in the subset of severely-ill non-intubated COVID-19 patients and were compared to a control group.…”
mentioning
confidence: 99%
“…T = 260 C = 969 Ip et al 2020 [23] Retrospective 547 Tocilizumab had no statistically significant benefit in ICU survival. T = 134 C = 413 Wadud et al 2020 [24] Retrospective 94 Tocilizumab was associated with increased survival for patients requiring mechanical ventilation T = 44 C = 50 Capra et al 2020 [25] Prospective 85 Tocilizumab was associated with improved in-hospital survival T = 62 C = 23 (hydroxychloroquine and lopinavir/ritonavir) Rossi et al 2020 [26] Retrospective 168 Tocilizumab was associated with improved survival and freedom from ventilation T = 84 C = 84 T, treatment group (tocilizumab); C, control group [27] Prospective Lopinavir/ritonavir 80 Favipiravir showed more 14-day chest CT scan improvement and sooner viral clearance compared to lopinavir/ritonavir T = 35 C = 45 T, treatment group (favipiravir); C, control group significantly different among the groups. Remdesivir was also started late in some of the study patients.…”
Section: Discussionmentioning
confidence: 99%
“…Tocilizumab presents with mixed results. Half of the studies report no significant benefit compared to standard therapy [21][22][23], while the other half report improvement for severe cases or improved hospital stay, survival, and freedom from ventilation [24][25][26]. No studies assessed the duration of positive-to-negative SARS-CoV2 conversion.…”
Section: Treatmentmentioning
confidence: 99%